Age-dependent pathogenic profiles of enterotoxigenic Escherichia coli diarrhea in Bangladesh - Akhtar, Marjahan; Begum, Yasmin Ara; Isfat Ara Rahman, Sadia; Afrad, Mokibul Hassan; Parvin, Nasrin; Akter, Afroza; Tauheed, Imam; Amin, Mohammad Ashraful; Ryan, Edward T.; Khan, Ashraful Islam; Chowdhury, Fahima; Bhuiyan, Taufiqur Rahman; et al. (Frontiers in Public Health, 2024)
BackgroundAge plays a significant role in susceptibility to enterotoxigenic Escherichia coli (ETEC) infections, yet the distribution of ETEC virulence factors across age groups remains understudied. This study investigated the differential pathogenic profiles ETEC across various age groups, emphasizing the importance of selecting potential ETEC antigens tailored to infection patterns in infants and adults in Bangladesh.MethodsThis study utilized the icddr,b’s 2% systematic hospital surveillance data of diarrheal patients (n = 14,515) from 2017 to 2022 to examine the age-specific pathogenesis and clinical manifestations of ETEC infections.ResultsIn total ETEC was identified in 1,371 (9.4%) of surveillance samples. ETEC-associated diarrhea was higher in children aged 0–2 years and decreased significantly in the 3–17 years age group. Among all ETEC cases, 56% were adults (p = 0.0079) with severe dehydration. Distinct age-specific distribution of ETEC toxin types and colonization factors (CFs) were observed: heat labile toxin (LT)-associated ETEC infections decreased with age (p < 0.0001), while heat stable toxin (ST)-associated-ETEC was prevalent across all ages. Adults exhibited significantly higher rates of ETEC diarrhea with strains secreting both types of toxins. A high prevalence of antimicrobial resistance among ETEC strains, particularly in pediatric cases, with significant resistance observed against commonly used antibiotics such as azithromycin and in line with similar age specific toxin profiles. The most common CFs were CFA/I, CS3, CS5, CS6, and CS21. CFA/I positive ETEC infection was more common in children (p < 0.001), while CS5 and CS6 were more common in adults (p < 0.0001).ConclusionThe findings provide valuable insights into ETEC epidemiology, pathogenesis, and clinical manifestations. These observations imply that age-related differences in host-pathogen interactions exist for ETEC infections and this may influence the development of targeted vaccines or therapeutics and use in specific populations.